Influence Of Organizing Functions, Direction Functions And Planning Functions On Nurse Performance At Hospital Royal Prima Medan - Dennis Wijaya; Ermi Girsang; Sri Lestari Ramadhani; Sri Wahyuni Nasution; Ulina Karo Karo (International Journal of Health and Pharmaceutical (IJHP), 2022)
The optimal implementation of the managerial function of the head of the room is one of the factors that affect the performance of the team leader and has an impact on the quality of nursing services. Phenomena that occur in hospitals are often the head of the room busy with meeting activities held by hospital management so that the implementation of the role and function of the head of the room as a clinical supervisor who becomes a consultant for team leaders in nursing care is often neglected.The results of the study using product moment analysis found that there was an effect of implementing the managerial function of the head of the room on the performance of the team leader (p = 0.00 r = 0.905). The results of multiple linear regression showed that only the implementation of the planning function influenced the team leader's performance (p = 0.039 B = 4.150). The conclusion is that the higher the implementation of the planning function carried out by the head of the room, the better the performance of the team leader. The implications for nursing in this research are that it is necessary to improve the ability of the planning function of the head of the room through strategic planning training and developing nursing managerial concepts.